2021
DOI: 10.1108/ajems-08-2020-0389
|View full text |Cite
|
Sign up to set email alerts
|

Policy asymmetries and fiscal sustainability: evidence from Nigeria

Abstract: PurposeThis study examines and compares different specifications of the fiscal policy rule in the fiscal sustainability analysis of Nigeria.Design/methodology/approachThis is methodologically achieved by estimating the baseline constant-parameter and Markov regime switching fiscal models. The asymmetric autoregressive distributed lag fiscal model is also employed to substantiate the differential responses of fiscal authorities to public debt.FindingsThe baseline constant-parameter fiscal model provides mixed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Positive oil price shocks may spur white elephant projects that are not productive and cause inflationary pressures. It may be difficult to cut spending during AJEMS 14,4 periods of falling oil prices, leading fiscal authorities to finance budgets via borrowing; posing debt unsustainability (Moshiri, 2015;Adeosun et al, 2021b).…”
Section: Pt P Tà1mentioning
confidence: 99%
See 1 more Smart Citation
“…Positive oil price shocks may spur white elephant projects that are not productive and cause inflationary pressures. It may be difficult to cut spending during AJEMS 14,4 periods of falling oil prices, leading fiscal authorities to finance budgets via borrowing; posing debt unsustainability (Moshiri, 2015;Adeosun et al, 2021b).…”
Section: Pt P Tà1mentioning
confidence: 99%
“…This makes it crucial for policymakers to consider geopolitical risks in their decision-making regarding price and food inflation targeting. Price instability raises risk premia in interest rates, the cost of doing business, and causes investment and output to dwindle, which can have adverse effects on economic growth (Adeosun et al ., 2021a, b, c). In oil-dependent and developing economies where a substantial proportion of total consumption is characterized by food products, oscillatory oil prices resulting in food inflation can pose challenges to the conduct of monetary policy.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers suggested that microfinance institutions should provide financial education and training to local entrepreneurs to manage the finances effectively and make informed business decisions. In [19] In [20] conducted a study in Nigeria to evaluated microfinance towards poverty alleviation and economic growth in rural areas. The study found that microfinance institutions can help to reduce poverty and promote economic growth by providing financial support to small businesses engaged in tourism-related activities.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the increasing significance of the SSA's investment potential, domesticinvestments in key sectors remain below capacity in augmenting capital and labor inputs and in attaining these aforementioned milestones. The region faces huge investment financing gaps, investment generation efficiency constraints coupled with debt accumulation without a commensurate improvement in investment (Kodongo and Ojah, 2016;Adeosun et al, 2020Adeosun et al, , 2021. With unresolved fiscal issues, empirical research into the effectiveness of domesticinvestment towards inclusive growth is critical.…”
Section: Introductionmentioning
confidence: 99%